2020
DOI: 10.17485/ijst/v13i24.958
|View full text |Cite
|
Sign up to set email alerts
|

Impact of novel Coronavirus (COVID-19) pandemic on travel pattern: A case study of India

Abstract: Background: The outbreak of coronavirus disease 2019 (COVID-19) has been declared a pandemic by the World Health Organisation (WHO). The outbreak not only affects human health but also travel psychology. Objective and methodology: In order to understand the impact of coronavirus on the travel pattern of Indian people, this study adopts descriptive research techniques to compare travel scenarios during the normal situation, pre-lockdown, and till the COVID-19 pandemic end. The questionnaire included the informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 3 publications
3
48
0
1
Order By: Relevance
“…• Section 4: feelings and perceptions onboard public and private vehicles which allowed to acquire data on the state of anxiety, fear, and stress of post-pandemic people during travel activities, also assessing the propensity for alternative modes of transportation and alternative working methods such as prolongation of remote working times. In the previous studies, descriptive statistics [7,8] and the decision tree approach [9] were applied. This has been a relatively new research area; therefore, a prediction modeling, such as binary or ordinal regression, for gaining a deeper understanding has not been applied yet.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…• Section 4: feelings and perceptions onboard public and private vehicles which allowed to acquire data on the state of anxiety, fear, and stress of post-pandemic people during travel activities, also assessing the propensity for alternative modes of transportation and alternative working methods such as prolongation of remote working times. In the previous studies, descriptive statistics [7,8] and the decision tree approach [9] were applied. This has been a relatively new research area; therefore, a prediction modeling, such as binary or ordinal regression, for gaining a deeper understanding has not been applied yet.…”
Section: Methodsmentioning
confidence: 99%
“…The survey-based studies [7][8][9] suggested that the COVID-19 pandemic had a significant influence on urban travel patterns. The use of shared mobility during the pandemic period decreased 35% compared to before the pandemic and road users became more dependent on private mobility modes (i.e., cars, bicycles, and e-scooters) [7].…”
Section: The State-of-the-art Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The outbreak's damage has greatly affected the global economy, and all humanity will suffer the outcomes. By the end of September 2020, Covid-19 cases have crossed 34 million in which present active cases are only 7.8 million, and deaths crossed https://www.indjst.org/ over one million globally (1,2) . If the spread continues, the damage will be catastrophic, and it will take years to overcome the sequences.…”
Section: Introductionmentioning
confidence: 99%